1988
DOI: 10.1001/jama.1988.03410010070037
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis and Steroid-Responsive, Diffuse Interstitial Lung Disease

Abstract: We describe a patient with ulcerative colitis and extracolonic manifestations in whom diffuse interstitial pulmonary disease developed that was responsive to glucocorticoid therapy one year after total proctocolectomy. The patient presented in December 1983 with a subacute course marked by cough and progressive exertional dyspnea, abnormal chest examination results, and a chest roentgenogram that revealed diffuse interstitial and alveolar infiltrates. A transbronchial biopsy specimen revealed a polymorphic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Only four out of the 24 cases mentioned colectomy, including two cases (2/4, 50%) in which the ILD occurred subsequent to the colon resection (3,18), suggesting that the colectomy may be a stimulus for the occurrence of UC complicated by ILD. The two cases in which the ILD occurred prior to the colectomy were in different situations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Only four out of the 24 cases mentioned colectomy, including two cases (2/4, 50%) in which the ILD occurred subsequent to the colon resection (3,18), suggesting that the colectomy may be a stimulus for the occurrence of UC complicated by ILD. The two cases in which the ILD occurred prior to the colectomy were in different situations.…”
Section: Discussionmentioning
confidence: 98%
“…Among the 24 cases, 10 (11–13) did not report the order of the ILD and UC incidences. In 12 cases (12/14, 85.71%) the ILD occurred 1–15 years after the diagnosis of UC (3,4,7–9,1418); this included only five cases in which the ILD occurred during active UC (5/12, 41.67%) (3,4,14,15). In two cases it was reported that the ILD occurred prior to the UC (17,19); in one of these cases (19) the ILD occurred immediately subsequent to the UC relapse, indicating that UC activity may be associated with the incidence of ILD.…”
Section: Discussionmentioning
confidence: 99%
“…BOOP, a kind of interstitial pneumonitis, is rarely associated with UC. [16][17][18][19] There have been four reported cases of UC coexistent with BOOP. [16][17][18][19] In these patients, BOOP occurred at various stages of UC and there was a symptomatic and radiological alleviation of pneumonia and UC with steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] There have been four reported cases of UC coexistent with BOOP. [16][17][18][19] In these patients, BOOP occurred at various stages of UC and there was a symptomatic and radiological alleviation of pneumonia and UC with steroid therapy. One hypothesis is that both the lung and the colon are vulnerable to autoantibodies; both BOOP and UC have been associated with circulating immune complexes, and altered effector-cell function has been described in both disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation